DEVELOPMENT OF DIRECT BIOAUTOGRAPHY AS REFERENCE METHOD FOR TESTING ANTIMICROBIAL ACTIVITY OF GENTAMICIN AGAINST Escherichia coli - COLORADO R., Jhonny; GALEANO J., Elkin; MARTÍNEZ M., Alejandro (Vitae, 2009)
Bioautography is a fast and simple technique which combines the advantages of thin layer chromatography separation and antimicrobial activity detection. This technique displays directly antimicrobial fraction spots from a mixture. Efficacy determination of the technique improves the isolation of antimicrobial substances from complex mixtures. This article describes how bioautography is useful to quantify antimicrobial activity of amino glycoside gentamicin, against pathogen Escherichia coli (E. coli). Quantitative analysis is verified measuring diffusion halos diameters and applying different concentrations of gentamicin on tlc plates. Volume effect is measured on variability of results. Differences between diffusion halos and microbial inhibition are analyzed too. Results show how antibiotic diffusion on tlc plates is a determining factor, and there is a concentration range where strong interactions between measured variables led to establish a method to be validated for detecting and quantifying antimicrobial substances from complex mixtures.